2022
DOI: 10.1136/ijgc-2021-003001
|View full text |Cite
|
Sign up to set email alerts
|

Global challenges of radiotherapy for the treatment of locally advanced cervical cancer

Abstract: Cervical cancer represents a significant portion of the global cancer burden for women, with low- and middle-income countries carrying the bulk of this burden. Additionally, underserved populations in countries with sufficient resources may have a higher incidence of cervical cancer and poorer outcomes. Concurrent chemoradiotherapy is the standard-of-care treatment for locally advanced cervical cancer, which includes patients with stage IB3 to IVA disease, and it is effective for many patients; however, cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 55 publications
0
42
0
2
Order By: Relevance
“…In the real world, penetration of techniques and an indication of possibilities of new modalities for radiation techniques will be necessary to monitor and survey the technical advantages 15. To successfully perform global clinical trials of cervical cancer, including concurrent chemoradiotherapy plus brachytherapy and immuno-oncology, novel standardization of radiotherapy will be resolutely required in the future 16…”
Section: International Obstacles and Approachesmentioning
confidence: 99%
“…In the real world, penetration of techniques and an indication of possibilities of new modalities for radiation techniques will be necessary to monitor and survey the technical advantages 15. To successfully perform global clinical trials of cervical cancer, including concurrent chemoradiotherapy plus brachytherapy and immuno-oncology, novel standardization of radiotherapy will be resolutely required in the future 16…”
Section: International Obstacles and Approachesmentioning
confidence: 99%
“…Cervical cancer is the fourth most common cancer and the most common gynecological malignancy ( 139 ), of which squamous cell carcinoma (SCC) is the most common type, accounting for approximately 80% of all cervical cancers ( 140 ). Treatment of advanced cervical cancer includes surgery, chemotherapy, and radiation therapy, but cervical cancer mortality remains high ( 141 ), mainly related to CSCs ( 142 ). Studies have suggested that ALDH1 can be used as a cervical CSC marker ( 143 , 144 ), which can lead to resistance to chemotherapy and is closely related to a poor prognosis ( 145 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%
“…It has an incidence-mortality rate of 14.9–7.6 and 22.5–11.5 per 100,000 people on a Latin American and national level, respectively [ 1 ], thus making it one of the most costly oncologic pathologies for the health system. Compared with countries with a high level of resources, like the United States or Western European countries, developing countries like Peru and Indonesia, which have limited monetary and educational resources in healthcare, have the highest CC incidence and mortality rates [ 2 ]. CC is the fourth most common type of cancer in women under 45 [ 3 ], yet the average at diagnosis with CC is 51 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with countries with a high level of resources, like the United States or Western European countries, developing countries like Peru and Indonesia, which have limited monetary and educational resources in healthcare, have the highest CC incidence and mortality rates [ 2 ]. CC is the fourth most common type of cancer in women under 45 [ 3 ], yet the average at diagnosis with CC is 51 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%